STRUCTURAL CHARACTERIZATION AND STORAGE STABILITY OF HEAT-INDUCED LACTOFERRIN-SODIUM CASEINATE COMPLEXES AT DIFFERENT MASS RATIOS - Sun, Yaping (Food and Feed Research, 2026)
Sodium caseinate (NaCas) forms complexes with lactoferrin (LF), yet the structural characteristics and stability of these complexes before and after heating are not well understood. This study demonstrated that lactoferrin and sodium caseinate exhibit weak electrostatic interactions prior to heating. Upon heating at 90 °C for 10 minutes, these interactions were significantly enhanced, resulting in the formation of stable lactoferrin/sodium caseinate complexes at ratios of 2:1 and 1:1. Complexes formed at a 1:2 ratio initially exhibited smaller particle sizes and lower turbidity but subsequently precipitated during storage. Conversely, complexes at 2:1 and 1:1 ratios maintained consistent turbidity and particle size over 20 days, indicating excellent long-term stability. These findings reveal the important role of NaCas in stabilizing LF during heat treatment and storage, providing valuable insights for the development of stable protein-based functional food ingredients.
Keywords: colloidal stability; heat treatment; turbidity; particle size; cation exchange chromatography; zeta potential